Strengthening Entrepreneurship Education Through the Market Day Program - M Topit Hidayat; Mufida Tullaili; Susi Evanita; Armiati Armiati (Universitas Negeri Padang, 2024)
This study aims to determine the influence of two independent variables, namely the Market Day demonstration learning method (X1) and the TCL learning method (X2), on the dependent variable, which is learning outcomes (Y). This research uses a quasi-experimental design and targets all students of Nirwana Kindergarten. Random sampling was used to determine the division between the experimental and the control classes, with a total sample of 31. The Market Day demonstration learning method was used in the experimental group, while the Teacher-Centered Learning (TCL) method was used in the control group. The findings indicate that the Market Day demonstration learning method significantly improves students' learning outcomes in the experimental group, thereby validating the effectiveness of this approach in enhancing students' learning outcomes.